2007
DOI: 10.1002/jnr.21358
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced neuronal differentiation in a three‐dimensional collagen‐hyaluronan matrix

Abstract: Efficient 3D cell systems for neuronal induction are needed for future use in tissue regeneration. In this study, we have characterized the ability of neural stem/progenitor cells (NS/PC) to survive, proliferate, and differentiate in a collagen type I-hyaluronan scaffold. Embryonic, postnatal, and adult NS/PC were seeded in the present 3D scaffold and cultured in medium containing epidermal growth factor and fibroblast growth factor-2, a condition that stimulates NS/PC proliferation. Progenitor cells from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 37 publications
6
117
0
Order By: Relevance
“…17 Another study used a collagen and hyaluronan scaffold to grow embryonic, postnatal, and adult neural stem and progenitor cells. 18 Early differentiating human embryonic stem cells were further induced to differentiate in a 3D scaffold made of poly(lactic-co-glycolic acid)/poly(L-lactic acid). 19 Finally, one study compared the viability of hippocampal neurons and astrocytes grown on 2D conditions with that of cells grown on an aragonite 3D scaffold prepared from coralline exoskeleton, showing better results for the 3D cultures.…”
Section: Introductionmentioning
confidence: 99%
“…17 Another study used a collagen and hyaluronan scaffold to grow embryonic, postnatal, and adult neural stem and progenitor cells. 18 Early differentiating human embryonic stem cells were further induced to differentiate in a 3D scaffold made of poly(lactic-co-glycolic acid)/poly(L-lactic acid). 19 Finally, one study compared the viability of hippocampal neurons and astrocytes grown on 2D conditions with that of cells grown on an aragonite 3D scaffold prepared from coralline exoskeleton, showing better results for the 3D cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Functional synapses have been observed in three-dimensional neuronal cultures at similar or earlier time points compared to 2D models (O'Shaughnessy et al, 2003;van Vliet et al, 2007). Furthermore, neural stem/progenitor three-dimensional cell cultures showed an increased differentiation into neurons compared with 2D cultures (Brannvall et al, 2007). the phenotype of microglial cells is highly dependent on the culture conditions.…”
Section: Issues and Future Challenges To Be Addressed By 3d In Vitro mentioning
confidence: 72%
“…Moreover three-dimensional cultures often show enhanced survival and neuronal differentiation compared to traditional monolayer cultures (Brannvall et al, 2007;Peretz et al, 2007). the enhanced survival could be related to the improved cell-cell and cell-matrix contact, as it improves cell signaling and gap junction connections, but these factors may need further investigation, as also in vivo survival after, e.g., injection of cells in the brain is still not clarified (Hansson et al, 2000;Schierle et al, 1999).…”
Section: Benefits and Advantages Of Neuronal 3d Modelsmentioning
confidence: 99%
“…As to the micro-environment cues, Akhavan et al reported accelerated differentiation of neural stem cells cultivated on ginseng-reduced graphene oxide sheets [33]. It is addressed that a three-dimensional collagen-hyaluronan matrix could enhance neuronal differentiation [34]. Francis et al demonstrated that preconditioning the human embryonic stem cell with hypoxic environment and its derived cytoprotective phenotype may promote the neural differentiation and enhanced cell survival rates [35].…”
Section: Effects Of Fluid Flow Shear Stress On Rbmscsmentioning
confidence: 99%